In Painful Shoulder Disease, Inpatient Rehabilitation has Long Term Benefits with or without Therapeutic Nuclear Magnetic Resonance: A Randomized Controlled Clinical Trial - Werner Kullich; Barbara Stritzinger; Monika Mustak-Blagus; Albrecht Falkenbach; Jutta Rus-Machan; Thomas Berger; Bibiane Steinecker-Frohnwieser (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2016)
Introduction: The aim of the presented study was to investigate the effect of an inpatient rehabilitation stay with application of therapeutical nuclear magnetic resonance therapy (NMRT) in 150 patients with painful shoulder diseases in a controlled trial. Methods: In a double blinded placebo-controlled multicenter study during a three-week inpatient rehabilitation pain, sleep quality, shoulder function, respectively biomarkers for stress and pain by treatment series with therapeutical nuclear magnetic resonance (NMRT) applied as an additive treatment with a series of NMR on nine consecutive days (9 x 1h) was investigated. Results: Virtually all (except sleep quality) investigated parameters, mainly pain (VAS) and function (Quick Dash) improved significantly during and after the rehabilitation programme in both study groups. We found no additional effect between the group that received rehabilitation without NMRT and the group with rehabilitation programme plus active NMRT at any time of the six month follow up.  Conclusion: In fact, a good outcome of the rehabilitation programme became obvious whereas, the NMR therapy did not result in a verifiable, additive effect. Therefore, one might consider that a possible positive effect by the NMRT on painful shoulder affections is masked by the obviously effective rehabilitation programme to treat the very complex shoulder joint.